Friedman Curve Positively Correlates with Cesarean Section and Oxytocin Augmentation in Active Phase Delivery as Compared to Partograph - Anak Agung Ngurah Anantasika; I Wayan Artana Putra; Ida Bagus Putra Adnyana; I Wayan Megadhana; Ryan Saktika Mulyana; Agustinus Darmawan Hariyanto (Indonesian Society of Obstetrics and Gynecology, 2023)
Objective: To investigate the correlation between cesarean section and oxytocin augmentation in childbirth monitored with the Friedman curve compared to the World Health Organization (WHO) partographs. Methods: An analytic cross-sectional study was conducted from March to May 2021, involving mothers giving birth whose delivery process was monitored using either the Friedman curve or the WHO partograph (n=28 for each group) at Wangaya Hospital in Denpasar City. The duration of the active phase until delivery, occurrence of cesarean section, and administration of oxytocin augmentation were assessed using the Friedman curve and the WHO partograph. The normality of the data was tested using the Kolmogorov-Smirnov test, and the Spearman correlation test was employed to measure the direction and strength of the correlation. Results: There was no signifi cant difference between the groups in terms of monitoring the active phase until delivery using the Friedman curve compared to the WHO partograph (p=1.000 > 0.05). Maternal monitoring with the Friedman curve showed a positive correlation with the occurrence of cesarean section compared to the WHO partograph (r=0.296, p=0.027). Additionally, monitoring childbirth with the Friedman curve exhibited a positive correlation with the administration of oxytocin augmentation compared to the WHO partograph (r=0.298, p=0.026). Conclusion: The fi ndings suggest a stronger positive correlation between the incidence of cesarean section and the administration of oxytocin augmentation in childbirth monitored with the Friedman curve compared to the WHO partograph. Keywords: cesarean section, Friedman curve, oxytocin augmentation, WHO partograph. Abstrak Tujuan: Untuk menentukan korelasi antara operasi sesar dan augmentasi oksitosin pada persalinan yang dipantau dengan kurva Friedman dibandingkan dengan partograf Organisasi Kesehatan Dunia (WHO). Metode: Desain penelitian analitik potong lintang dilakukan pada Maret-Mei 2021, dengan melibatkan ibu bersalin yang proses persalinannya dipantau menggunakan kurva Friedman atau Partograf WHO (n=28 untuk setiap kelompok) di ruang bersalin di Rumah Sakit Wangaya, Kota Denpasar. Waktu fase aktif hingga kelahiran bayi, persalinan seksio sesarea, dan augmentasi oksitosin dinilai dengan menggunakan kurva Friedman dan Partograf WHO. Uji normalitas dilakukan dengan uji Kolmogorov-Smirnov, dilanjutkan dengan uji korelasi Spearman untuk mengukur arah dan kekuatan korelasi. Hasil: Pemantauan ibu bersalin dengan kurva Friedman dibandingkan dengan Partograf WHO dalam hal fase aktif-persalinan bayi menunjukkan tidak ada perbedaan yang signifi kan di antara kedua kelompok (p = 0,000 > 0,05). Pemantauan ibu dengan kurva Friedman berkorelasi positif dengan kejadian bedah sesar dibandingkan dengan Partograf WHO (r = 0,296, p = 0,027). Selain itu, pemantauan persalinan dengan kurva Friedman berkorelasi positif dengan pemberian oksitosin dibandingkan dengan partograf WHO (r = 0,298, p = 0,026). Kesimpulan: Terdapat korelasi positif yang lebih tinggi antara kejadian bedah sesar dan pemberian augmentasi oksitosin pada proses persalinan yang dipantau dengan kurva Friedman dibandingkan dengan partograf WHO. Kata kunci: augmentasi oksitosin, kurva friedman, partograf WHO, seksio sesarea